Characteristics of Balinese architectural fat houses in Denpasar City - Suyasa, I Putu Suta; Parwata, I Wayan; Mahaputra, I Nyoman Gede; Wahyuni, Putu Ika (Gema Wiralodra, 2023)
This research aims to find factors that influence the characteristics of flats with a Balinese architectural perspective and plan a design model for apartments in Bali based on the concept of Balinese architecture. The research method used is a combination of quantitative and qualitative methods. The first stage uses quantitative methods, and the second stage uses qualitative methods. The research sample was taken using nonprobability random sampling with a sample size of 200 respondents. Data analysis was done through univariate analysis by presenting tables, pictures, and graphs. The results of the research show that the factors that influence the characteristics of flats with a Balinese architectural style include the principles of spatial planning with the choice of location in the city of Denpasar, the principles of building layout with a 3-story flat building height, and the selection of building facades with a Balinese architectural style, the principles of utilities and facilities which include green open space, lift facilities, traditional and cultural facilities, centralized parking facilities, easily accessible merchant facilities, health, education, and an integrated and organized waste processing system. Apart from that, Balinese architectural principles such as Tri Hita Karana and the Hulu Teben concept are also used as references. Principles of building layout with a 3-story apartment building height and the selection of Balinese architectural style building facades, principles of utilities and facilities which include green open space, lift facilities, traditional and cultural facilities, centralized parking facilities, merchant facilities, health, easy education accessible, and an integrated and organized waste processing system. Apart from that, Balinese architectural principles such as Tri Hita Karana and the Hulu Teben concept are also used as references. Principles of building layout with a 3-story apartment building height and the selection of Balinese architectural style building facades, principles of utilities and facilities which include green open space, lift facilities, traditional and cultural facilities, centralized parking facilities, merchant facilities, health, easy education accessible, and an integrated and organized waste processing system. Apart from that, Balinese architectural principles such as Tri Hita Karana and the Hulu Teben concept are also used as references.